The 2-hour job search : using technology to get the right job faster - Dalton, Steve, 1976- (Tantor Media, Inc., 2022)
Use the latest technology to target potential employers and secure the first interview with these revised and updated tools and recommendations. Technology has changed not only the way we do business, but also the way we look for work. The 2-Hour Job Search rejects laundry lists of conventional wisdom in favor of a streamlined job search approach that produces results quickly and efficiently. In three steps, creator Steve Dalton shows you how to select, prioritize, and make contact with potential employers so you can land that critical first interview. In this revised second edition, you'll find updated advice on how to efficiently surf online job postings, how to reach out to contacts at your dream workplace and when to follow up, and advice on using LinkedIn, Indeed, and Google to your best advantage. Dalton incorporates ideas from leading thinkers in behavioral economics, psychology, and game theory, as well as success stories from fans of the first edition. The 2-Hour Job Search has been shared at schools across the globe and is a formal part of the curriculum for all first-year MBAs at Duke University. With this book, you'll learn how to make it work for you too.